Tuning of thioredoxin redox properties by intramolecular hydrogen bonds. - Åsmund Kjendseth Røhr; Marta Hammerstad; K Kristoffer Andersson (PLoS ONE, 2013)
Thioredoxin-like proteins contain a characteristic C-x-x-C active site motif and are involved in a large number of biological processes ranging from electron transfer, cellular redox level maintenance, and regulation of cellular processes. The mechanism for deprotonation of the buried C-terminal active site cysteine in thioredoxin, necessary for dissociation of the mixed-disulfide intermediate that occurs under thiol/disulfide mediated electron transfer, is not well understood for all thioredoxin superfamily members. Here we have characterized a 8.7 kD thioredoxin (BC3987) from Bacillus cereus that unlike the typical thioredoxin appears to use the conserved Thr8 side chain near the unusual C-P-P-C active site to increase enzymatic activity by forming a hydrogen bond to the buried cysteine. Our hypothesis is based on biochemical assays and thiolate pKa titrations where the wild type and T8A mutant are compared, phylogenetic analysis of related thioredoxins, and QM/MM calculations with the BC3987 crystal structure as a precursor for modeling of reduced active sites. We suggest that our model applies to other thioredoxin subclasses with similar active site arrangements.